Narasi Human Interest Dalam Buku "Totto-Chan : Gadis Cilik di Jendela" - Shandi Andreansyah; Sumaina Duku; Jufrizal . (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
This study analyzes the human‑interest narrative in the book Totto‑Chan: The Little Girl at the Window from a journalistic perspective. The research questions are: How is the human‑interest narrative presented in the book when viewed from a journalistic perspective? And How do journalistic narrative techniques construct human‑interest values in the book? The objectives are to analyze the presentation of human‑interest narrative in Totto‑Chan from a journalistic viewpoint, and examine the journalistic narrative techniques used to build human‑interest values. Theoretical grounding employs Teun A. van Dijk’s concept of human interest in discourse analysis, which explains how texts are structured to evoke attention, emotion, empathy, and reader engagement through human elements. This research uses a qualitative, descriptive‑analytic approach. Data collection is documentary (library) study, with primary data (the Totto‑Chan text) and secondary sources (related literature). The main research location is Gramedia Palembang, as the site for accessing the children’s literature collection and the translated Japanese edition. Data are analyzed qualitatively using systematic content analysis to identify themes, narrative strategies, and journalistic language elements that contribute to human‑interest value. The study aims to reveal patterns of human‑interest presentation and the journalistic narrative techniques that strengthen readers’ emotional involvement in Totto‑Chan.